DEVELOPMENT OF CAR TRAFFIC VOLUMES ORGANIZATION METHODS IN THE RUSSIAN EMPIRE AND IN THE USSR - Kozachenko, D. M.; Papakhov, O. Y.; Hermaniuk, Y. N. (Science and Transport Progress, 2020)
Purpose. The main purpose of this article is to study the development of methods for organizing car traffic volumes into trains at the railways of the Russian Empire and the USSR. Methodology. The studies were carried out based on an analysis of literary sources and methods of the theory of organization of operational work of railways. Findings. The methods for organizing car traffic volumes have gone a significant development path under the influence of changes in the working conditions of railway transport, the formation of control technology and mathematical methods of optimization. The emergence of scientific methods for organizing car traffic volumes in trains dates back to the times of the Russian Empire. A modern approach to the organization of car traffic volumes is based on the plan for the train formation, developed in the USSR in 1931–1945. The goal of the implementation of the train formation plan was to reduce railroad expenses for cargo transportations. The conditions for the implementation of this approach is that the railways are vertically integrated: they simultaneously operate the railway infrastructure, and are the carriers transporting goods in their cars, while there is no competition between the transport modes for freight traffic volumes. The formation of modern methods for solving the problem of organizing car traffic volumes was mainly performed in 1945–1952. The basis of these methods is the separation of the organization of car traffic volumes into separate subtasks and their sequential solution in a deterministic and static setting. In practice, the organization of car traffic volumes at the railways of the USSR was solved in the 1970–1980s using a computer. The transition of Ukraine to a market model of the economy has led to a significant change in the working conditions of railway transport, which requires a review of the principles of organizing car traffic volumes into trains. Originality. For the first time, based on a historical analysis of the development of methods for organizing car traffic volumes at the railways of the Russian Empire and the USSR, connections were established between the working conditions of railway transport and methods for organizing car traffic volumes into trains. Practical value lies in the fact that they indicate the need to change in Ukraine the organization of car traffic volumes in accordance with the current working conditions of railway transport and the chosen direction of reforming the railway transportation market.